The Relationship Between Competency And Job Choices Of Sewing Training Graduates At Mukomuko Vocational Training Center Bengkulu - Weska Zulma Friningsih; Alim Harun Pamungkas (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research was motivated by the low competence of graduates of sewing training at the Mukomuko Bengkulu Job Training Center. This is because the competence of graduates is still lacking. This research aims to; (1) describe the competence of sewing training graduates at the Mukomuko Bengkulu Job Training Center, (2) describe the job choices of sewing training graduates at the Mukomuko Bengkulu Job Training Center, (3) and see the relationship between competence and job choices for sewing training graduates at the Mukomuko Job Training Center Bengkulu. This type of research is quantitative correlation with the population, namely the graduates of the second and third batches of sewing training in 2020 at the Mukomuko Bengkulu Job Training Center as many as 32 people. The technique used for sampling is using saturated sampling technique. The sample in this study was taken as much as 100% totaling 32 people. For data collection using a questionnaire technique, while for data collection tools using a questionnaire in the form of statement items, and then the analysis in this study uses percentages and product moments. The results of this study indicate that; (1) the competency of sewing training graduates at the Mukomuko Bengkulu Job Training Center is still low (2) the job choice of sewing training graduates at the Mukomuko Bengkulu Job Training Center is also still low, and there is a significant relationship between competence and job choice of sewing training graduates at the Job Training Center Mukomuko Bengkulu. The hope of this research is that competence and training programs are further improved. Keywords: Competence, Job Choice